Estudo e implementação de web services utilizando Zend Framework - Silva, Pablo Henrique (2011)
Along with the growth of the search for solutions that are agile and productive began to emerge the first tools known as frameworks This paper focuses on show in a theoretical way and use the Zend Framework in the development of web service, pointing out its benefits in the development of web applications MVC (Model-View-Controller) on PHP 5.